Regioselective One‐Pot Synthesis of Triptycenes via Triple‐Cycloadditions of Arynes to Ynolates - Umezu, Satoshi; dos Passos Gomes, Gabriel; Yoshinaga, Tatsuro; Sakae, Mikei; Matsumoto, Kenji; Iwata, Takayuki; Alabugin, Igor; Shindo, Mitsuru (Angewandte Chemie International Edition, 2017)
We developed the novel one‐pot synthetic method of substituted triptycenes by the reaction of ynolates and arynes. This four‐step process involves three cycloadditions and electrocyclic ring opening of the strained Dewar anthracene. Each of the three related but structurally distinct classes of nucleophiles (ynolate, enolate, and anthracenolate) reacts with o‐benzyne in the same predictable manner controlled by chelation and negative hyperconjugation. The resulting functionalized C3‐symmetrical triptycenes hold promise in the design of functional materials. Three alkynes and one triple bond: The title reaction constitutes a four‐step process involving three cycloadditions and electrocyclic ring opening of the strained Dewar anthracene. Each of the three related but structurally distinct classes of nucleophiles (ynolate, enolate, and anthracenolate) reacts with o‐benzyne in the same predictable manner controlled by chelation and negative hyperconjugation.